Cyber Cooperation. (Beijing Review, 2013)
The article informs that China's Assistant Foreign Minister Zheng Zeguang has reiterated on May 29, 2013 that it is against all Internet hacking attacks and is hoping to cooperate with the U.S. on this matter under the principle of mutual respect and trust.